1997
DOI: 10.1038/bjc.1997.457
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of allelic loss in skin tumours from immunosuppressed individuals

Abstract: Summary Organ transplant recipients receiving immunosuppression show a dramatically increased risk of non-melanoma skin cancer. The cause of this increase is not known. We report that the rate of loss of heterozygosity (at all the loci we examined) was significantly lower in tumours from immunosuppressed individuals than in tumours from immunocompetent subjects [20 out of 148 (14%) vs 157 out of 428 (37%); P < 0.0001]. These results suggest that tumours in immunosuppressed individuals have a different molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 14 publications
4
11
3
Order By: Relevance
“…These results, however, are in keeping with a previous study which reported less allelic loss at chromosome 9p in skin tumors from immunosuppressed compared with immunocompetent patients (Rehman et al, 1997). The explanation for these findings remain elusive, but one could speculate that the significantly higher prevalence of human papillomavirus found in immunosuppressed cutaneous SCC obviates the need for direct genetic/epigenetic TSG alterations, similar to the mechanism proven in anogenital carcinomas (Harwood and Proby, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…These results, however, are in keeping with a previous study which reported less allelic loss at chromosome 9p in skin tumors from immunosuppressed compared with immunocompetent patients (Rehman et al, 1997). The explanation for these findings remain elusive, but one could speculate that the significantly higher prevalence of human papillomavirus found in immunosuppressed cutaneous SCC obviates the need for direct genetic/epigenetic TSG alterations, similar to the mechanism proven in anogenital carcinomas (Harwood and Proby, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…This observation and the results of our study suggest that perhaps the suppression of the immune system in OTRs may influence the development of SCCs in these patients. This phenomenon has been reported before by Rehman et al, who demonstrated that the LOH rate in SCCs from OTRs was less than half of that in SCCs from immunocompetent patients [43]. Moreover, there could also be a direct effect of the applied immunosuppressive drugs on the molecular pathogenesis of SCCs in OTRs, which has also been suggested before by others [44].…”
Section: Discussionsupporting
confidence: 76%
“…Tumours in patients receiving immunosuppressive therapy showed a low frequency of AI. Similar findings have been reported by Rehman et al (1997), who suggested that tumours that develop in immunosuppressed patients in which there may be decreased immunosurveillance, may be able to bypass the need to inactivate certain tumour suppressor proteins. Inclusion of a high proportion of stage 1 and 2 tumours in this analysis has identified several cases with small interstitial deletions at key chromosomal loci, and our data support the existence of several tumour suppressor gene areas at the short arms of chromosomes 3, 8 and 9.…”
Section: Discussionsupporting
confidence: 74%